1989
DOI: 10.1128/aac.33.4.418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antibiotic dose, dosing interval, and duration of therapy on outcome in experimental pneumococcal meningitis in rabbits

Abstract: We examined the influence of several pharmacokinetic parameters on cure rates in rabbits with experimental pneumococcal meningitis. When the duration of treatment was kept constant, cure rates improved as the individual dose of ampicillin was increased. On the other hand, when four doses of ampicillin at 60 mg/kg of body weight, producing peak concentrations in cerebrospinal fluid (CSF) of approximately 40 times the MBC, were administered at intervals of 24 instead of 4 h and the duration of therapy was thus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…For ␤-lactam agents, peak concentrations in CSF at least 10-fold greater than the MBC are required for therapeutic effectiveness (24,25). In the present study, the rate of bacterial clearance was similar for the two treatment regimens, and peak CSF vancomycin concentrations that were four-to eightfold greater than the MBC were adequate for bactericidal activity.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…For ␤-lactam agents, peak concentrations in CSF at least 10-fold greater than the MBC are required for therapeutic effectiveness (24,25). In the present study, the rate of bacterial clearance was similar for the two treatment regimens, and peak CSF vancomycin concentrations that were four-to eightfold greater than the MBC were adequate for bactericidal activity.…”
Section: Discussionsupporting
confidence: 53%
“…Prior experimental meningitis studies suggested that, for ␤-lactam antibiotics, peak concentrations in CSF correlate with bactericidal activity and that concentrations in CSF at least 10-fold greater than the minimum bactericidal concentration (MBC) for the pathogen are required for optimal bacterial killing (24,25). For vancomycin, the range of concentrations in CSF considered therapeutic and the pharmacodynamic index that best predicts outcome are not known.…”
mentioning
confidence: 99%
“…Experts in CNS infection advocate that effective bactericidal activity of ␤-lactams in the CSF is quantified most appropriately through measurement of the T>MBC. 16 Unfortunately, the MBC of the pathogens in both cases was not reported by the clinical microbiology laboratory, which is consistent with the standard of care used in the hospital setting. The T>MBC associated with the use of meropenem as a prolonged infusion in our two patients was not known, and confirmation of bactericidal activity was not available.…”
Section: Discussionmentioning
confidence: 55%
“…Animal infection models have substantiated that for the ␤-lactams in the CSF, the component of time of exposure, as opposed to concentration, is most highly correlated with bacterial killing activity. [16][17][18] However, the parameter of time in these experiments was indexed to microbiologic activity of the drug through the MBC and not the MIC. Experts in CNS infection advocate that effective bactericidal activity of ␤-lactams in the CSF is quantified most appropriately through measurement of the T>MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial treatment is essential for reducing the number of viable bacteria in invasive pneumococcal infection. Beta-lactam treatment timing with regard to the kinetics of bacterial growth inhibition was reported by Tauber et al for the rabbit meningitis model (13). Cure rates were improved as the dose of penicillin was increased and the interval between doses was increased.…”
mentioning
confidence: 79%